Gestational diabetes mellitus: to screen or not to screen; that is the question!. Issue 8 (August 2016) - Cuschieri, Sarah; Savona-Ventura, Charles
Abstract: Any screening programme must be sufficiently cost-effective and applicable to conditions where early intervention can alter the disease progression. Gestational diabetes (GDM) qualifies as a condition amenable to screening since timely intervention can alter the development of short and long-term complications in both the mother and child. While the gold standard for screening remains the 75 g oral glucose tolerance test, it is essential that conformity in diagnostic cut-off criteria is generally agreed upon and should be based on outcome clinical indicators rather than statistical or economic indicators. A clear clinical sub-division classification of GDM based on the severity of the condition also needs to be universally defined. The 2013 WHO guidelines serve to establish a general consensus, though it is accepted that further studies need be performed to confirm some of the proposals.